2019
DOI: 10.1101/860676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Topology of Mutated Driver Pathways

Abstract: Much progress has been made, and continues to be made, towards identifying candidate mutated driver pathways in cancer. However, no systematic approach to understanding how candidate pathways relate to each other for a given cancer (such as Acute myeloid leukemia), and how one type of cancer may be similar or different from another with regard to their respective pathways (Acute myeloid leukemia vs. Glioblastoma multiforme for instance), has emerged thus far. Our work attempts to contribute to the understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In a companion study (Dridi et al, 2019), we expand the work reported here to address a topological perspective on pathways. We first formalize our tunable parameter concept using methods of algebraic topology.…”
Section: Discussionmentioning
confidence: 89%
“…In a companion study (Dridi et al, 2019), we expand the work reported here to address a topological perspective on pathways. We first formalize our tunable parameter concept using methods of algebraic topology.…”
Section: Discussionmentioning
confidence: 89%